Coating composition, coated member, and method for producing coated member

By using epoxy resin and cellulose nanofibers in the coating composition to control their concentration and viscosity, the problems of sag and coating performance in the coating parts are solved, and efficient coating and corrosion resistance are achieved.

CN119325497APending Publication Date: 2025-01-17ASTEMO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280096868.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-07-12
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In the coating component, the surface coating coating composition extending along the surface is prone to sag, and the prior art is difficult to take into account good coating performance when suppressing the sag.

Method used

Using a coating composition containing epoxy resin and cellulose nanofibers, the introduction rate of cellulose nanofibers is 0% or more and 10% or less, and the concentration of solid components is 0.05% or more and 10% or less, and the viscosity is controlled. The sagging is suppressed by the mesh structure of CNF and good coating performance is maintained at 2.8 dPa·s or more and 350 dPa·s or less.

Benefits of technology

Effectively suppress sag during coating, maintain coating performance, improve the water and acid resistance of the coating film, and reduce manufacturing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325497A_ABST
    Figure CN119325497A_ABST
Patent Text Reader

Abstract

The coating composition according to the present invention comprises a resin containing an epoxy resin as a main component, and cellulose nanofibers in which a functional group different from a hydroxyl group is introduced into a glucose unit at an introduction rate of 0-10%, inclusive, of a hydroxyl group moiety. The concentration of the cellulose nanofibers relative to the solid content is 0.05% by mass or more and 10% by mass or less, and the viscosity of the coating composition is 2.8 dPa * s or more and 350 dPa * s or less. The amount of the epoxy resin and / or the solvent is adjusted such that the content of the cellulose nanofibers relative to the entire coating composition is 0.03-10 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating composition, a coated component, and a method for producing the coated component. Background Art

[0002] The abstract of Patent Document 1 states that "The epoxy resin coating composition of the present invention is characterized in that it contains an epoxy resin, a curing agent for the epoxy resin, and cellulose nanofibers. In addition, the coating reinforcing agent of the present invention is characterized in that cellulose nanofibers are dispersed in a polyester resin. Furthermore, the method for producing the coating reinforcing agent of the present invention is characterized in that a mixture of powders of a polyester resin and cellulose fibers is pressurized and kneaded, and the method for producing the epoxy resin coating composition of the present invention is characterized in that the coating reinforcing agent is blended." [Prior art literature] [Patent Document]

[0003] Patent Document 1: Japanese Patent Publication No. 2019-183004 Summary of the invention [Technical problem to be solved by the invention]

[0004] Among the parts coated with the coating composition, there are known parts such as propeller shafts having surfaces extending in all directions. In such parts, when the coating composition is applied to a surface having an angle relative to the horizontal direction, the applied coating composition is prone to flow along the surface. However, in the technology described in Patent Document 1, the flow of the applied coating composition is not considered. On the other hand, if the viscosity is only increased to suppress the flow, the coating performance is reduced. The technical problem to be solved by the present invention is to provide a coating composition, a coated component, and a method for producing a coated component that can achieve both suppression of sagging during coating and good coating performance. [Technical solutions for solving technical problems]

[0005] The coating composition of the present invention comprises a resin and cellulose nanofibers, wherein the resin contains an epoxy resin as a main component; the introduction rate of functional groups different from hydroxyl groups into the cellulose nanofibers is 0% or more and 10% or less, the concentration of the cellulose nanofibers relative to the solid content is 0.05% or more and 10% or less by mass, and the viscosity of the coating composition is 2.8 dPa·s or more and 350 dPa·s or less. Other solutions are described in the mode for implementing the invention. [Effects of the invention]

[0006] According to the present invention, it is possible to provide a coating composition, a coated component, and a method for producing a coated component that can achieve both suppression of sagging during coating and good coating performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 It is a cross-sectional view of a coated component of the present invention. Figure 2 This is a flow chart showing the method for producing a coated component according to the present invention. DETAILED DESCRIPTION

[0008] Below, while referring to the attached Figure 1 The method for implementing the present invention (referred to as an embodiment) is described. In the description of the following embodiment, other embodiments applicable to an embodiment are also described appropriately. The present invention is not limited to the following embodiment, and different embodiments may be combined or arbitrarily deformed within the scope that does not significantly damage the effect of the present invention. In addition, the same figure marks are marked on the same components, and repeated descriptions are omitted. In addition, the same names are marked on components with the same functions. The contents in the drawings are only schematically represented. For the convenience of illustration, they can be changed according to the actual structure within the scope that does not significantly damage the effect of the present invention, or the illustration of some components in the drawings can be omitted or deformed.

[0009] The coating composition of the present invention comprises a resin and cellulose nanofibers (CNF), wherein the resin comprises an epoxy resin as a main component. The coating composition of the present invention is applied to a substrate 2 ( Figure 1 ). The coated component 1 ( Figure 1 ).

[0010] In the coating composition of the present invention, epoxy resin has the highest content among all resins. All resins in the coating composition of the present invention may be epoxy resins. Epoxy resins are, for example, modified epoxy resins, preferably single-component curable epoxy resins. Epoxy resins may be, for example, manufactured from bisphenol A and epichlorohydrin. The number average molecular weight of the epoxy resin is arbitrary, for example, it may be greater than 100 and less than 5000. In addition to epoxy resins, the resin may contain any resin as long as it does not significantly impair the effects of the present invention.

[0011] CNF is obtained, for example, by finely cutting cellulose fibers composed of glucose β-1,4 bonds. CNF is preferably a natural material, and is obtained, for example, by mechanically defibrillating cellulose fibers in pulp obtained from broadleaf trees.

[0012] In the CNF of the present invention, in the part of the hydroxyl group in the glucose unit, the introduction rate of the functional group different from the hydroxyl group into the hydroxyl group is 0% or more and 10% or less. By containing such CNF, the change of the physical property of CNF caused by the functional group different from the hydroxyl group can be suppressed, and the influence on the coating product caused by the change of the physical property of CNF can be suppressed. In CNF derived from nature, the introduction rate is usually 0% or more and 10% or less, preferably about 0% (that is, almost unsubstituted). As a functional group that can be introduced, for example, a carboxyl group that can be generated by oxidation of the -CH2OH group is included, but it is not limited to this. Whether a functional group other than the functional group derived from cellulose is introduced can be judged by, for example, spectrum analysis based on infrared absorption spectroscopy.

[0013] The average fiber diameter of CNF is not particularly limited, for example, it is 4 nm or more and 100 nm or less. By setting it to 4 nm or more, chemical modification of CNF can be suppressed, and changes in the physical properties of CNF caused by the modification can be suppressed. Furthermore, the coating 3 ( Figure 1 On the other hand, by setting the size to 100 nm or less, CNF can be easily dispersed evenly in the coating composition, thereby easily coating the substrate 1 ( Figure 1 ) coating. In addition, after coating, the effect of CNF can be exerted in the entire area of ​​the coating composition. For example, the fiber average diameter can be determined by extracting any 10 CNFs in the TME image obtained by shooting the cross section of CNF and calculating the average value of each diameter.

[0014] In the coating composition of the present invention, resin and CNF are usually included as solid components. The "solid component" mentioned here refers to a substance that contributes to the formation of a coating film after drying (a substance that remains as a solid. A substance that functions as a coating film.). Therefore, the solid component is usually a component other than volatile components (solvents, etc.) in the coating composition of the present invention. In the case where the coating composition contains only resin, CNF and solvent, the solid component is consistent with the total amount of resin and CNF. In addition, in the case where the coating composition also contains an arbitrary component (a component other than volatile components. For example, pigments, metal particles, etc.), the solid component is consistent with the total amount of resin, CNF and the arbitrary component. The arbitrary component can be dissolved in a solvent or dispersed in a solvent. In addition, the resin and CNF can also be dissolved in a solvent or dispersed in a solvent respectively.

[0015] The concentration of CNF relative to the solid content is 0.05% by mass or more, the upper limit is 9% by mass or less, preferably 0.3% by mass or less. By setting it to 0.05% by mass or more, the liquid sagging during coating can be suppressed, and the viscosity of the coating composition can be reduced. Accordingly, it can be easily coated and good coating performance can be exerted. On the other hand, by setting it to 10% by mass or less, the viscosity of the coating composition can be suppressed from being too large, and good coating performance can be improved. In addition, by setting it to 0.3% by mass or less, the coating film 3 ( Figure 1 )'s acid resistance.

[0016] In the coating composition of the present invention, the viscosity is 2.8 dPa·s or more and 350 dPa·s or less. By setting the viscosity within this range, it is possible to achieve both the suppression of sagging during coating and good coating performance. For example, the viscosity can be measured using a B-type viscometer.

[0017] The relationship between CNF concentration and viscosity is described. In the coating composition of the present invention, the viscosity is determined by the total value of the viscosity of the coating itself and the viscosity caused by the high viscosity achieved by the network formed by CNF. Therefore, if the viscosity of the coating alone is low, the final viscosity will also decrease relatively after adding CNF. Therefore, as the effect of adding CNF, the effect of suppressing sagging achieved by the network structure of CNF and the effect of suppressing sagging achieved by the final viscosity of the coating composition are different effects. Therefore, there is not necessarily a correlation between CNF concentration and viscosity.

[0018] It is preferred to adjust the amount of at least one of the epoxy resin or the solvent so that the content of CNF relative to the solid component is 0.12% by mass or more, the upper limit is 6% by mass or less, preferably 0.3% by mass or less. By setting it to 0.03% by mass or more and 10% by mass or less, it is possible to take into account both the suppression of sagging during the coating of the coating composition and good coating performance. In particular, by setting it to 0.03% by mass or more, the 3D mesh structure possessed by CNF can be used to reduce the fluidity when standing, and it is expected to suppress the coating film 3 ( Figure 1 ) deviation. Through the reinforcement effect brought by such a 3D mesh structure, it is also possible to expect improved crack resistance, increased hardness of the coating film, improved impact resistance, etc. In addition, by setting it to 0.3% by mass or less, the coating film 3 ( Figure 1 )'s acid resistance.

[0019] The solvent that can be used is not particularly limited as long as it can dissolve the epoxy resin and disperse CNF. As the solvent, for example, organic solvents such as triethylamine, ethylene glycol monopropyl ether, 3-methyl-3-methoxybutanol, and ethylene glycol monoethyl ether can be listed. As the solvent, in addition to using an organic solvent, an aqueous solvent can also be used at the same time. For example, the aqueous solvent can include at least one of water, any aqueous solution, etc. The solvent can be used only one, or two or more can be used in any ratio and combination.

[0020] Figure 1 2 is a cross-sectional view of a coated component 1 of the present invention. The coated component 1 has a substrate 2 and a coating film 3 disposed on the surface of the substrate 2. The details will be described later, but the substrate 2 is not limited thereto, and may be, for example, a transmission shaft. Figure 1 In the figure, as an example, a transmission shaft and a rotating shaft ( Figure 1 A cross-sectional view in a direction perpendicular to the paper plane).

[0021] The coating film 3 comprises the above-mentioned resin and the above-mentioned CNF. As described above, the resin contains an epoxy resin as a main component. As described above, the introduction rate of the hydroxyl part of the CNF that introduces a functional group different from the hydroxyl group into the glucose unit is 0% or more and 10% or less, and the concentration relative to the coating film 3 is 0.05% by mass or more and 9% by mass or less. The coating film 3 is obtained by applying the coating composition of the present invention, for example, to the substrate 2 and drying it. The details of these resins and CNF are the same as the description of the above-mentioned coating composition, so the description is omitted.

[0022] The substrate 2 includes, for example, a curved surface, and the coating film 3 is arranged on the surface of the curved surface. As described above, the coating composition of the present invention can suppress sagging during coating. Therefore, even when coating is performed on the curved surface of the substrate 2, sagging can be suppressed, and a coating film 3 with uniform film thickness can be easily obtained. The substrate 2 can include a plane, and the coating film 3 can be formed on the plane. In particular, for example, even if coating is performed on a plane configured to have an inclination in the horizontal direction, sagging can be suppressed, and the details will be described later. Such a substrate 2 is, for example, a transmission shaft as described above.

[0023] The thickness of the coating film 3 is, for example, 30 μm or more. By setting the coating film 30 to such a thickness, the functions of the resin and CNF, such as corrosion resistance, can be easily exerted. The upper limit of the thickness of the coating film 3 is not particularly limited, and may be, for example, 100 μm or less.

[0024] Figure 2 The coating component 1 ( Figure 2 ) is a flow chart of a manufacturing method (hereinafter referred to as the manufacturing method of the present invention). The manufacturing method of the present invention includes a coating step S1 and a drying step S2.

[0025] The coating step S1 is to coat the coating composition of the present invention onto a stationary substrate 2 ( Figure 1 ) surface. The concentration of CNF in the coating composition relative to the solid content and the coating film 3 ( Figure 1 ) is consistent with the content of CNF in the coating. The coating method is not particularly limited, for example, any method such as a sprayer, a brush, etc. can be used for coating. Among them, it is preferred to carry out the coating step S1 by using at least one of a sprayer or a brush. As described above, since the coating composition of the present invention is not easy to sag during coating, it is possible to suppress sag by a simple method. In particular, the coating composition of the present invention having the above-mentioned viscosity is not easy to use a spray method, but since CNF has thixotropy, the fluidity increases during spray coating, thereby enabling spray coating.

[0026] As the configuration mode of the substrate 2, the substrate 2 can be configured in a manner that the surface of the substrate 2 extends in the horizontal direction, or in a manner that the surface of the substrate 2 has an angle relative to the horizontal direction. Among them, it is preferred to carry out the coating step S1 by applying the coating composition of the present invention on a surface having an angle θ relative to the horizontal direction. Accordingly, even for a substrate 2 configured in a manner that would produce sagging if a coating composition in the prior art is used, the generation of sagging can be suppressed. The angle θ referred to here is greater than 0°, and as an upper limit, for example, is less than 90°, preferably 45° or less, and more preferably 30° or less.

[0027] Furthermore, when painting a flat surface, it is preferable to arrange the flat surface so that the flat surface has an angle θ with respect to the horizontal direction. Figure 1 As shown, when a curved surface is painted, the angle θ is the angle of the tangent to the horizontal direction, with the tangent to the curved surface as the reference. The angle θ can be the same or different in the entire area of ​​the painted surface. When a curved surface is painted, the angle θ usually varies depending on the painting position.

[0028] It is preferred that the coating film 3 ( Figure 1 ) is applied in a manner such that the thickness is, for example, 20 μm or more, preferably 30 μm or more, thereby performing the coating step S1. Thus, the function of the coating film 3 formed by the coating and drying of the coating composition of the present invention can be fully exerted. In addition, for example, the thickness to which the coating composition of the present invention is applied can be determined based on the solid content concentration in the coating composition of the present invention to achieve the desired thickness. That is, the greater the solid content concentration, the thicker the thickness, and the smaller the solid content concentration, the thinner the thickness.

[0029] The drying step S2 is a step of drying the substrate 2 coated with the coating composition of the present invention in a static state. The drying step S2 is preferably performed at room temperature, specifically, preferably in an atmosphere of 15° C. to 30° C. Thus, the solvent in the coating composition can be removed while suppressing the influence on the resin and CNF in the coating composition.

[0030] In the case where the substrate 2 has a face extending downwardly vertically, if the coating composition in the prior art is used for coating, gravity plays a role just after coating, and the coating composition is easy to sag. The sag of the coating composition can cause the thickness of the coating film 3 to decrease, and the corrosion resistance decreases. On the other hand, if the coating amount of the coating composition is increased in order to ensure the thickness of the coating film 3, the mass increase of the coating component 1, the increase in the man-hours for manufacturing, and the increase in the time until drying will occur. In addition, when drying, it is also considered to use hot air to promote drying to shorten the time, but due to the use of hot air, the large-scale manufacturing facilities and the increase in man-hours will be generated. However, in the coating composition of the present invention, as described above, the suppression of sag during coating and good coating performance are taken into account. Accordingly, the coating component 1 can be lightweighted while fully ensuring corrosion resistance, and the increase in man-hours during manufacturing can be suppressed. Example

[0031] Hereinafter, the present invention will be described in more detail with reference to Examples. Note that all the preparations and evaluations described below were performed at 23° C. In addition, according to the provisions of JIS Z8703, the temperature has a range of ±2° C.

[0032] <Preparation of the coating composition of the present invention> The physical properties of the CNF used are as follows. Average fiber diameter: 10nm~100nm Chemical modification: None (introduction rate 0%) Component: Cellulose monomer Main raw material: broadleaf trees (derived from natural sources) Defibrination method: Mechanical defibrination (physical defibrination) Manufacturer: Daio Paper Manufacturing Co., Ltd.

[0033] The resin used is a modified epoxy resin. The concentration of the resin relative to the entire coating composition is a prescribed concentration of 15 to 25 mass %. As a solvent, a mixed solvent of water and an organic solvent is used. The concentration of water relative to the entire coating composition is a prescribed concentration of 30 to 40 mass %, and the concentration of the organic solvent relative to the entire coating composition is a prescribed concentration of 10 to 15 mass %. The organic solvent is a mixed solvent of triethylamine, ethylene glycol monopropyl ether, 3-methyl-3-methoxybutanol, and ethylene glycol monoethyl ether.

[0034] The CNF, resin and solvent described above are fully mixed to prepare the coating composition of the present invention. The following Table 1 shows the liquid sag and coating performance when the CNF concentration relative to the solid content of the coating composition and the viscosity of the coating composition are adjusted to the values ​​in the following Table 1. Unless otherwise specified below, the evaluation method of the liquid sag and coating performance is carried out in the same manner as in the following Example 1.

[0035] [Table 1] Table 1:

[0036] In Table 1, the meanings of the symbols in the liquid sag property and coating performance are as follows. Liquid dripping ○ No liquid dripping occurs. △Liquid dripping hardly occurs, but dripping will occur if the film thickness increases. ×Liquid sagging occurs immediately after painting. Coating performance ○ Painting can be performed without causing scratches. △ There is a tendency to be easily worn, and there are unevenness of brush marks on the coating film, but it can be painted and the base is not revealed in appearance. × Large scratches occurred, or the coating composition did not separate from the brush and coating could not be performed.

[0037] <Evaluation of sagging and coating performance based on CNF concentration and viscosity> The following evaluations were conducted using some of the coating compositions having the components shown in Table 1 above.

[0038] Example 1 (corresponding to test number 12 in Table 1 above) A coating composition having a CNF concentration of 8.05% by mass relative to the solid content and a viscosity of 320 dPa·s measured by a B-type viscometer was prepared, and a cylinder imitating a transmission shaft was coated with a brush. Drying was performed at a specified temperature of 15°C or more and 30°C or less. The film thickness (wet film thickness) before drying was 190 μm. After coating, the coating was dried in a static state. The film thickness after drying was 128 μm. As a result of coating, although there was a tendency to easily scratch, coating was possible. In addition, due to the high viscosity, liquid sagging did not occur.

[0039] Example 2 (corresponding to test number 11 in Table 1 above) The coating was carried out in the same manner as in Example 1 except that the CNF concentration was changed to 6.71 mass % and the viscosity was changed to 260 dPa·s. The film thickness before drying (wet film thickness) was 250 μm, and the film thickness after drying was 138 μm. The coating result was that although scratches were easily generated, the coating was possible. In addition, due to the high viscosity, liquid sagging did not occur.

[0040] Example 3 (corresponding to test number 2 in Table 1 above) The concentration of CNF was changed to 0.08 mass %, the viscosity was changed to 2.8 dPa·s, and the coating was performed using a sprayer instead of a brush. Other than that, the coating was performed in the same manner as in Example 1. The film thickness (wet film thickness) before drying was 80 μm, and the film thickness after drying was 45 μm. As a result of coating and drying, the coating can be performed uniformly without scratching. In addition, when the film thickness before drying reaches 80 μm or less, the coating can be performed without sagging.

[0041] Comparative Example 1 (corresponding to Test No. 13 in Table 1 above) The coating was carried out in the same manner as in Example 1 except that the concentration of CNF was changed to 9.68 mass % and the viscosity was changed to 380 dPa·s. The viscosity of Comparative Example 1 was outside the viscosity range of the coating composition of the present invention. The evaluation result showed that the coating composition was not separated from the brush due to the high viscosity, and thus could not be coated. In addition, when the coating was separated from the brush by applying a physical force for coating, large scratches were confirmed. However, due to the high viscosity, no liquid dripping occurred.

[0042] Comparative Example 2 (corresponding to Test No. 1 in Table 1 above) The coating was performed in the same manner as in Example 1 except that the concentration of CNF was changed to 0.03% by mass, the viscosity was changed to 2.7 dPa·s, and the coating was performed using a sprayer instead of a brush. In Comparative Example 2, the concentration of CNF relative to the solid content was outside the CNF concentration range of the coating composition of the present invention. The film thickness before drying (wet film thickness) was a maximum of 80 μm, and the film thickness after drying was 37 μm. As a result of coating and drying, sagging occurred immediately after coating. However, it was possible to apply uniformly by spray coating.

[0043] <Evaluation of sagging based on CNF content> Example 4 The same method as in Example 1 was used to evaluate whether or not sagging occurred, except that the CNF concentration (solid content basis) was set to 0.1 mass %. As a result, no sagging occurred when the film thickness before drying (wet film thickness) was 190 μm or less. In addition, after drying, a coating film 3 ( Figure 1 ).

[0044] Example 5 The evaluation was performed in the same manner as in Example 4 except that the average fiber diameter of CNF was set to 100 nm or more and 1000 nm or less. As a result, similar to Example 4, no sagging occurred when the film thickness was 190 μm or less, but the texture became matte. The film thickness after drying was 91 μm.

[0045] Example 6 The evaluation was performed in the same manner as in Example 4 except that the CNF concentration (solid content basis) was 0.5 mass %. As a result, no sagging occurred when the film thickness was 190 μm or less, as in Example 4. After drying, a glossy coating film 3 having a film thickness of 101 μm was obtained.

[0046] Comparative Example 3 The evaluation was performed in the same manner as in Example 4 except that CNF was not used. As a result, sagging occurred when the coating reached a film thickness of 130 μm. After drying, a glossy coating film 3 was obtained.

[0047] <Dispersibility Evaluation> Example 7 When the coating composition of Example 1 was visually observed, no CNF precipitate was observed, thus confirming that the CNF was uniformly dispersed.

[0048] Reference Example 1 The evaluation was performed in the same manner as in Example 7 except that the average fiber diameter of CNF was set to 100 nm or more and 1000 nm or less. As a result, it was found that CNF precipitated and CNF was not uniformly dispersed. Therefore, it was found that in order to uniformly disperse CNF, the average fiber diameter of CNF was preferably 100 nm or less.

[0049] <Water resistance evaluation> Next, a water resistance test was performed.

[0050] Example 8 (corresponding to test number 6 in Table 1 above) The CNF and resin described at the beginning of the example were used so that the CNF concentration as the solid content concentration was 1.13 mass %, and the viscosity was adjusted to 3.5 Pa·s. Thus, the coating composition of the present invention was prepared. Then, the coating component 1 ( Figure 1). During the preparation process, no sagging of the coating composition occurred. In addition, it was easy to apply and the coating performance was also good. The film thickness before drying (wet film thickness) was 60 μm, and the film thickness after drying was 24 μm. The prepared coated part 1 was subjected to a water resistance test. The water resistance test was performed by immersing in water at a specified temperature for a specified time. The result of the water resistance test was that there was no sagging on the coating film 3 ( Figure 1 ) was observed to have expansion, falling off, rust, etc.

[0051] Reference Example 2 Except that CNF was not used, the evaluation was performed in the same manner as in Example 8. As a result, no swelling, peeling, rust, etc. were observed in the appearance of the coating film 3.

[0052] Since CNF is hydrophilic, the water absorption of the coating composition containing CNF is enhanced, and the water resistance is easily reduced. However, even if CNF is contained, the coating composition according to the present invention can obtain excellent water resistance to the same degree as the coating composition of Reference Example 2 without CNF. The reason is that by adjusting the fiber diameter and compounding amount of CNF, the hydrophobicity of the coating film itself will not be greatly hindered despite the addition of CNF.

[0053] <Acid resistance evaluation> Next, an acid resistance test was performed.

[0054] Example 9 (corresponding to test number 4 in Table 1 above) The CNF and resin described at the beginning of the embodiment were used so that the CNF concentration as the solid content concentration was 0.15 mass %, and the viscosity was adjusted to 2.8 dPa·s using the above-mentioned mixed solvent. Thus, the coating composition of the present invention was prepared. Then, the coating component 1 ( Figure 1 ). During the preparation process, no sagging of the coating composition occurred. In addition, it is easy to apply and the coating performance is also good. The film thickness before drying (wet film thickness) is 50μm, and the film thickness after drying is 25μm. The prepared coated part 1 was subjected to an acid resistance test. The acid resistance test was performed by immersing in a strong acid aqueous solution at a specified temperature for a specified time. The result of the acid resistance test was that there was no sagging on the coating film 3 ( Figure 1 ) was observed to have expansion, falling off, rust, etc.

[0055] Example 10 The coating composition of the present invention was prepared in the same manner as in Example 9 except that the concentration of CNF was changed to 0.5 mass %. The film thickness before drying (wet film thickness) was 50 μm, and the film thickness after drying was 24 μm. The acid resistance test was performed on the prepared coated component 1, and swelling was observed in the appearance of the coating film 3.

[0056] Example 11 The coating composition of the present invention was prepared in the same manner as in Example 9 except that the concentration of CNF was changed to 0.3 mass %. The film thickness before drying (wet film thickness) was 50 μm, and the film thickness after drying was 27 μm. The prepared coated component 1 was subjected to an acid resistance test, and swelling was observed in the appearance of the coating film 3.

[0057] From the results of Example 9 and Reference Examples 2 and 3, it is understood that the acid resistance is improved by setting the CNF concentration to 0.3 mass % or less relative to the solid content. [Explanation of Reference Numerals]

[0058] 1: Coating structure; 2: Substrate; 3: Coating film.

Claims

1. A coating composition, characterized in that Contains resin and cellulose nanofibers, wherein The resin contains epoxy resin as a main component; The cellulose nanofiber has a hydroxyl group portion having a functional group different from a hydroxyl group introduced into a glucose unit at a rate of 0% or more and 10% or less, The concentration of the cellulose nanofibers relative to the solid content is 0.05 mass % or more and 9 mass % or less, The viscosity is 2.8 dPa·s or more and 350 dPa·s or less.

2. The coating composition according to claim 1, characterized in that The amount of at least one of the epoxy resin and the solvent is adjusted so that the content of the cellulose nanofibers relative to the solid content is 0.12% by mass or more and 6% by mass or less.

3. The coating composition according to claim 2, characterized in that The content of the cellulose nanofibers is 0.3 mass % or less.

4. The coating composition according to claim 1, characterized in that The average fiber diameter of the cellulose nanofibers is greater than 4 nm.

5. The coating composition according to claim 4, characterized in that The cellulose nanofibers have an average fiber diameter of 100 nm or less.

6. A coated component, characterized in that: A coating film is provided on a surface of the substrate and a substrate. The coating film comprises resin and cellulose nanofibers, wherein The resin contains epoxy resin as a main component; The cellulose nanofibers have a hydroxyl moiety introduction rate of a functional group different from a hydroxyl group introduced into a glucose unit of 0% to 10%, and a concentration thereof relative to the coating film of 0.05% to 9% by mass.

7. The coating component according to claim 6, characterized in that: The coating film has a thickness of 30 μm or more.

8. The coating component according to claim 6, characterized in that: The substrate comprises a curved surface, The coating film is disposed on the surface of the curved surface.

9. The coating component according to claim 8, characterized in that: The base body is a transmission shaft.

10. A method for manufacturing a coated component, characterized in that: It includes coating process and drying process, among which: In the coating step, a coating composition is coated on the surface of a stationary substrate, the coating composition comprising a resin containing an epoxy resin as a main component, and cellulose nanofibers having a hydroxyl portion introduction rate of 0% or more and 10% or less in which a functional group different from a hydroxyl group is introduced into a glucose unit, the concentration of the cellulose nanofibers relative to the solid content is 0.05% by mass or more and 9% by mass or less, and the viscosity of the coating composition is 2.8 dPa·s or more and 350 dPa·s or less; In the drying step, the substrate coated with the coating composition is dried in a stationary state.

11. The method for manufacturing a coated component according to claim 10, characterized in that: The coating step is performed by using at least one of a sprayer and a brush.

12. The method for manufacturing a coated component according to claim 10, characterized in that: The coating step is performed by applying the coating composition so that the thickness of the coating film formed after drying is 30 μm or more.

13. The method for manufacturing a coated component according to claim 10, characterized in that: The coating step is performed by coating the coating composition on a surface that is angled with respect to a horizontal direction.

14. The method for manufacturing a coated component according to claim 10, characterized in that: The drying step is performed in an atmosphere of 15° C. or higher and 30° C. or lower.

Citation Information

Patent Citations

  • Epoxy resin coating composition and manufacturing method therefor, and coating reinforcement agent and manufacturing method therefor

    JP2019183004A